Taxonomy of knowledge management systems in a complex environment - Ni, Pengcheng; Kantola, Jussi (United States, 2025)
In many fields of research, knowledge management systems (KMS) are considered to be an effective and comprehensive way of enhancing organizational knowledge and can contribute to the successful running of projects, especially in complex environments. This paper focuses on the application of a taxonomy charting the common characteristics of a KMS in the complex environment of the Smart European Shipbuilding project (SEUS), funded by the Horizon Europe programme. The paper reviews relevant literature on knowledge management and provides a comprehensive KMS taxonomy combined with practical application in a complex project. The taxonomy offers a useful tool for creating a KMS and related knowledge management strategy for projects in complex environments.
Keywords: Taxonomy, Knowledge management system, Complex environment
Human Factors, Business Management and Society